Using embodied learning technology to advance motor performance of children with special educational needs and motor impairments - Kosma, Panagiotis; Ioannou, Andri; Retalis, Symeon (My University, 2017)
Embodied learning, under the lens of Embodied Cognition theory, emphasizes on the inseparable link between brain, body and the world; it considers that the active human body can alter the function of the brain and therefore the cognitive process. From this perspective, the exploration of learning environments that promote bodily activity in relation to cognitive tasks are gaining the attention of the research community in the recent days. One such case is the use of multimodal, motion-based games mediated by sensors like a Kinect camera to enable learning through active and embodied interaction with learning content. This paper presents findings from an empirical investigation of using embodied touchless interactive games to enhance motor performance for children with learning disabilities and motor impairments. Young children, mainly attending special units within mainstream elementary schools, participated in a five-month intervention. Kinetic analytics, together with teachers’ self-reported observations and interviews, revealed improvements in children’s motor performance, particularly psychomotor ability and psychomotor speed. The paper contributes to the technology-enhanced learning community by providing insights into the use of embodied learning technology in special education.
Keywords: Embodied cognition; Embodied learning; Kinect; Learning disabilities; Motion-based games; Natural interaction; Special education; Technology-enhanced learning